The Influence of Contemporary Thinkers on Said’s Orientalism - Abedi Valoojerdi , Mohammad Hossein (Journal of Critical Studies in Language and Literature, 2020)
Orientalism (1978) is one of the greatest intellectual works of the last century in which Edward W. Said (1935-2003) challenges Western culture on account of its erroneous beliefs about the East. Orientalism, as Said describes, is not merely an academic field of study, but a way of thinking and a collection of beliefs which work together as a powerful tool to justify the colonial ideology. However, what Said suggests is not an anti-Western theory. In Orientalism, he interacts with a number of his contemporary intellectuals. This paper is a brief review of the influence of contemporary philosophers, thinkers and Western theories on Said’s interpretation of Orientalism. The paper also attempts to discuss that how Said’s Orientalism is related to the above-mentioned theories such as Gramsci’s cultural hegemony, Foucault’s notion of power/knowledge, Derrida’s deconstruction, and Bakhtin’s polyphony. Although this topic has been of interest to other researchers, further studies will contribute to the richness of the subject and can be used by students and scholars.